2011
DOI: 10.1208/s12248-011-9272-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Testing for Generic Drugs: An FDA Perspective

Abstract: In vitro dissolution testing is an important tool used for development and approval of generic dosage forms. The objective of this article is to summarize how dissolution testing is used for the approval of safe and effective generic drug products in the United States (US). Dissolution testing is routinely used for stability and quality control purposes for both oral and non-oral dosage forms. The dissolution method should be developed using an appropriate validated method depending on the dosage form. There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
126
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(134 citation statements)
references
References 5 publications
0
126
0
8
Order By: Relevance
“…15,16) The United States Pharmacopeia (USP) Apparatus 3 (Reciprocating cylinder or BioDis) was specifically designed for dissolution evaluation of MR dosage forms because it can mimic physicochemical and mechanical changes experienced by a MR dosage form in the GIT. [17][18][19] In addition, this apparatus demonstrates superior hydrodynamic controls in comparison to USP apparatuses 1 and 2 and provides numerous options in terms of instrumental parameters, such as composition of the media, pH and agitation rate. 20,21) To describe a relationship between in vitro characteristics of a dosage form and the in vivo response, a predictive mathematical model is used to define the in vitro-in vivo correlation (IVIVC) level.…”
mentioning
confidence: 99%
“…15,16) The United States Pharmacopeia (USP) Apparatus 3 (Reciprocating cylinder or BioDis) was specifically designed for dissolution evaluation of MR dosage forms because it can mimic physicochemical and mechanical changes experienced by a MR dosage form in the GIT. [17][18][19] In addition, this apparatus demonstrates superior hydrodynamic controls in comparison to USP apparatuses 1 and 2 and provides numerous options in terms of instrumental parameters, such as composition of the media, pH and agitation rate. 20,21) To describe a relationship between in vitro characteristics of a dosage form and the in vivo response, a predictive mathematical model is used to define the in vitro-in vivo correlation (IVIVC) level.…”
mentioning
confidence: 99%
“…La FDA promueve reducir el trámite regulatorio y los estudios innecesarios en humanos sin sacrificar la calidad de los productos (Anand, Yu y Conner, 2011). Las pruebas de disolución han emergido como una herramienta en la industria farmacéutica de genéricos, especialmente para los procesos de formulación y desarrollo, en el monitoreo de procesos de manufactura y en pruebas de control de calidad; también son de gran utilidad para predecir el desempeño in vivo de ciertos productos.…”
Section: Bioexención Y Sistema De Clasificación Biofarmacéutico (unclassified
“…The rates of in vivo pharmacokinetic studies and in vitro comparative dissolution tests found in the applications were respectively higher and lower in 2010, compared to those of 2011. The documentation of bioequivalence from in vivo trials is less advantage in terms of cost, time and safety and requires ethic and regulatory approbations, contrary to the in vitro dissolution studies that are more accessible, easier and shorter to achieve [5,17,18]. Therefore, the comparative in vitro dissolution studies were privileged by the majority of the applicants with some success.…”
Section: Types Of Bioequivalence Documentations and Rates Of Compliancementioning
confidence: 99%